Impact of Small and Medium Enterprises (SMEs) on Economic Revitalisation in Nigeria - Kolade Akinpelu Ayobami; Olatunji Olarenwaju Patrick; Ochei, Fidelia Ngozi (My University, 2024)
This study investigated the impact of small and medium enterprises (SMEs) on economic revitalisation in Nigeria from 1992 to 2022, using an ex-post facto research design and secondary data. The autoregressive distributed lag (ARDL) model was employed to assess the long-run relationship between SMEs and economic revitalisation, revealing a significant positive association. Several key determinants of economic revitalisation were identified, including investment, domestic credit to the private sector, inflation, labour, capital, and technology. Investment and domestic credit support business expansion and sustainability, while effective inflation management is crucial for maintaining economic stability. A skilled labour force, sufficient capital, and technological adoption are vital for economic progress. The findings indicate that SMEs play a critical role in driving Nigeria’s economic growth, while inflation and exchange rates have negative effects on economic revitalisation. The study concludes that investment, domestic credit, labour, capital, and technology are significant drivers of economic revitalisation, and the positive long-run relationship between SMEs and economic revitalisation underscores their importance. To enhance SME productivity and performance, the government should provide single-digit interest rates for domestic credit, enabling plant expansion and job creation. Furthermore, policies should ensure the accessibility of key economic factors, including investment, labour, technology, and capital, to practitioners. Robust monetary policies should be implemented to control inflation and exchange rates, which otherwise hinder SME growth and their contribution to economic revitalisation. In summary, the government should prioritise SME development as a core strategy for driving sustainable economic growth and stability in Nigeria.
Keywords: Capital; Economic; Investment; Labour; Revitalisation; SMEs; Technology